Respuesta :
The equivalent polynomial is 12x^2 -23x - 24.
You can get this by multiplying the two parenthesis by each other.
First start by multiplying the two front numbers:
4x * 3x = 12x^2
Then multiply the outermost numbers:
4x * -8 = -32x
Then multiply the innermost numbers:
3x * 3 = 9x
Then multiply the last numbers:
3* -8 = -24
Now combine all of them to get the above polynomial.
You can get this by multiplying the two parenthesis by each other.
First start by multiplying the two front numbers:
4x * 3x = 12x^2
Then multiply the outermost numbers:
4x * -8 = -32x
Then multiply the innermost numbers:
3x * 3 = 9x
Then multiply the last numbers:
3* -8 = -24
Now combine all of them to get the above polynomial.
[tex] = > (4x + 3)(3x - 8) \\ \\ = > 4x \times 3x - 4x \times 8 + 3x \times 3 - 8 \times 3 \\ \\ = > 12 {x}^{2} - 32x + 9x - 24 \\ \\ = > 12 {x}^{2} - 23x - 24[/tex]